Effect of a probiotic mixture of Bacillus subtilis 20Bp and Lactobacillus brevis 40Lp on productive and health indicators of broilers - Arteaga, Fátima; Rondón, Ana; Milián, Grrethel; Laurencio, Marta; Narváez, Gabriela; Velez, L. A.; Pinto, Georgette; Muñóz, J. (Cuban Journal of Agricultural Science, 2020)
To evaluate the probiotic effect of a mixture of Bacillus subtilis 20Bp and Lactobacillus brevis 40Lp on productive and health indicators of broilers, a total of 400 Cobb 500® chicks were used. A completely randomized design was applied and two treatments were established: control and probiotic, with 200 animals each. In the control, only the feeding formulas of the farm were applied, and in the probiotic a probiotic mixture was supplied, in doses of 1 mL per kg of food (109 ufc.g-1).The live weight, average daily gain, cumulative food intake and food conversion were calculated as productive indicators weekly recorded until the end of breeding. Among the health indicators, the viability and mortality were evaluated. It was found that the productive parameters improved with the use of the probiotic mixture, with an average daily gain of 65.61 g, while 56.96 g were produced in the control group. The application of the mixture improved the food conversion to 1.70, when compared to the control results (1.93, and the mortality was higher in the latter. It is concluded that the use of the probiotic mixture in the production of broilers favored the productive and health parameters evaluated. Key words: zootechnical additives, probiotics, birds.